Correlates of evidence-based nursing practice among nurses in Saudi Arabia: A structural equation model - Abuadas, Mohammad H (Belitung Nursing Journal, 2021)
Background: Consideration needs to be given to variables that impact the application of evidence-based nursing practice. Objective: This study aimed to generate and validate a structural model of factors predictive of evidence-based nursing practice. Methods: A cross-sectional descriptive design was used, with 612 registered nurses in the southern area of Saudi Arabia selected using a convenience sampling procedure. Data were collected during the period from November 2019 to January 2020 using valid and reliable questionnaires, including the novel Registered Nurses’ Competencies, Beliefs, Facilitators, Barriers, and Implementation of the Evidence-based Practice Questionnaire. A structural equation modeling technique was used for data analysis. Results: Evidence-based nursing practice was significantly influenced by nurses’ competency, beliefs, barriers, and facilitators. 38.75% of the variance was explained by all factors. Specifically, nurses’ beliefs partially mediated the relationship between nurses’ competency and the evidence-based application of nursing practice. In addition, the relationship between nurses’ beliefs and evidence-based application of nursing practice was partially mediated by organizational facilitators. Nurses’ competency and beliefs were significantly influenced by attending the workshop, education level, years of experience, and previous research work. Conclusion: The current study highlights the significant effect of personal and organizational variables toward the application of evidence-based nursing practice.